Admission code status and end-of-life care for hospitalized patients with COVID-19 - SİLİ, ULUHAN (My University, 2022)
© 2022 American Academy of Hospice and Palliative MedicineContext: The COVID-19 pandemic has highlighted variability in intensity of care. We aimed to characterize intensity of care among hospitalized patients with COVID-19. Objectives: Examine the prevalence and predictors of admission code status, palliative care consultation, comfort-measures-only orders, and cardiopulmonary resuscitation (CPR) among patients hospitalized with COVID-19. Methods: This cross-sectional study examined data from an international registry of hospitalized patients with COVID-19. A proportional odds model evaluated predictors of more aggressive code status (i.e., Full Code) vs. less (i.e., Do Not Resuscitate, DNR). Among decedents, logistic regression was used to identify predictors of palliative care consultation, comfort measures only, and CPR at time of death. Results: We included 29,923 patients across 179 sites. Among those with admission code status documented, Full Code was selected by 90% (n = 15,273). Adjusting for site, Full Code was more likely for patients who were of Black or Asian race (ORs 1.82, 95% CIs 1.5–2.19; 1.78, 1.15–3.09 respectively, relative to White race), Hispanic ethnicity (OR 1.89, CI 1.35–2.32), and male sex (OR 1.16, CI 1.0–1.33). Of the 4951 decedents, 29% received palliative care consultation, 59% transitioned to comfort measures only, and 29% received CPR, with non-White racial and ethnic groups less likely to receive comfort measures only and more likely to receive CPR. Conclusion: In this international cohort of patients with COVID-19, Full Code was the initial code status in the majority, and more likely among patients who were Black or Asian race, Hispanic ethnicity or male. These results provide direction for future studies to improve these disparities in care.
Keywords: Tıp; Dahili Tıp Bilimleri; Nöroloji; Cerrahi Tıp Bilimleri; Anesteziyoloji; Hemşirelik; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Neurology; Surgery Medicine Sciences; Anesthesiology; Nursing; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ANESTEZİYOLOJİ; HEMŞİRELİK; KLİNİK NÖROLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; ANESTHESIOLOGY; NURSING; CLINICAL NEUROLOGY; Genel Hemşirelik; Nöroloji (klinik); Anesteziyoloji ve Ağrı Tıbbı; General Nursing; Neurology (clinical); Anesthesiology and Pain Medicine; COVID; End of life; Palliative care